The Mediating Effect of Students' Perception and Satisfaction on the Relationship of Learning Environment and Accounting Career - Yusuf, Angeline Sugiarto; Mangoting, Yenni; Hoetomo, Melly Irna Natasya; Hatane, Saarce Elsye; Semuel, Hatane (Humaniora: Journal of Indonesia Culture and Society, 2021)
The research was inspired by accounting students’ failure to put their knowledge in line with their career choice in the accounting field, which in turn became a concern to higher education providers and accountant associations to be solved. The research aimed to discover accounting students’ intention to be an accountant in accounting education in Indonesia. Data were gathered through a survey with questionnaires involving accounting undergraduate students of both universities and colleges of private and govern as of vocational education in Indonesia. The 311 collected questionnaires were analyzed using Partial Least Square (PLS). The research proves that the learning environment is the main factor influencing students’ intention to pursue their careers in the accounting field. The learning environment as an external factor can alter either perception or perspective of accounting students concerning the accounting profession, affecting students’ intention to pursue a career in the accounting field. Another finding of the research is that perception of students’ beliefs built through interaction and experience of the learning environment elements can affect their satisfaction and intention to pursue a career in the accounting field.